Agriculture and rural development in Colombia 2011-2013: an approach - Cárdenas Pinzón, Johanna Inés; Vallejo Zamudio, Luis Eudoro (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The aim of this paper is to present a literature review of the concept of rural development and the role of agriculture and rural development in economic activity, and to determine the advances made in Colombia’s agricultural sector in the period 2011-2013, according to the proposed strategies for the sector in the National Plan of Development 2010-2014. It was concluded, in general terms, that agricultural policy in Colombia should be approached from the new vision of rural development, which must include activities taking place in rural areas, and the challenge should be rethinking the fact that the rural sector is limited only to the productive sector.